2021
DOI: 10.3389/fnagi.2021.685594
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebrospinal Fluid Profile of Cholesterol Metabolites in Parkinson’s Disease and Their Association With Disease State and Clinical Features

Abstract: Disordered cholesterol metabolism is linked to neurodegeneration. In this study we investigated the profile of cholesterol metabolites found in the cerebrospinal fluid (CSF) of Parkinson’s disease (PD) patients. When adjustments were made for confounding variables of age and sex, 7α,(25R)26-dihydroxycholesterol and a second oxysterol 7α,x,y-trihydroxycholest-4-en-3-one (7α,x,y-triHCO), whose exact structure is unknown, were found to be significantly elevated in PD CSF. The likely location of the additional hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…[120][121][122] Therefore, cholesterol is crucial for neuronal physiology, and cholesterol metabolism may be related to some central nervous system (CNS) diseases (Table 2), such as AD and Parkinson's disease (PD). [123][124][125][126][127][128]…”
Section: Cholesterol Metabolism In Neurological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…[120][121][122] Therefore, cholesterol is crucial for neuronal physiology, and cholesterol metabolism may be related to some central nervous system (CNS) diseases (Table 2), such as AD and Parkinson's disease (PD). [123][124][125][126][127][128]…”
Section: Cholesterol Metabolism In Neurological Diseasesmentioning
confidence: 99%
“…The consumption of cholesterol in neurons can impair the exocytosis, neuronal activity and neurotransmission of synaptic vesicles, leading to dendritic spines and synaptic degeneration 120–122 . Therefore, cholesterol is crucial for neuronal physiology, and cholesterol metabolism may be related to some central nervous system (CNS) diseases (Table 2), such as AD and Parkinson's disease (PD) 123–128 …”
Section: Cholesterol Metabolism In Neurological Diseasesmentioning
confidence: 99%
“…Chronic inflammation outside of the brain, such as NAFLD, was sufficient to induce neurodegeneration without genetic predisposition [ 87 ]. While this is happening, BAs are a significant aberrant biochemical route in PD patients, whether they are seen in the plasma, cerebral fluid, or intestinal tissues [ 104 , 105 , 106 , 107 , 108 , 109 ]. PD patients had significantly elevated plasma CA/CDCA and decreased glycoursodeoxycholic acid (GUDCA) [ 104 , 107 ], and the intensity of motor complaints was linked with taurine-conjugated bile acids [ 106 ].…”
Section: Bile Acid Alterations and Their Function In Brain Diseasementioning
confidence: 99%
“…Additionally, an examination of the data from Parkinson’s disease genome-wide association studies using an empirical Bayesian Lasso showed three significant pathways, including the main pathway for bile acid production [ 111 ]. 7α,(25R)26-dihydroxycholesterol and a second oxysterol 7α,x,y-trihydroxycholest-4-en-3-one (7α,x,y-triHCO) were found to be considerably higher in PD CSF, suggesting that the acidic pathway of bile acid production has been activated [ 108 ]. Unexpectedly, the appendix and ileum of Parkinson’s patients had higher levels of DCA and LCA, and hydrophobic and secondary bile acids [ 105 ].…”
Section: Bile Acid Alterations and Their Function In Brain Diseasementioning
confidence: 99%
“…There is now lot of evidence supporting that oxysterols formed by autoxidation such as 7-ketocholesterol (7KC) and 7β-hydroxycholesterol (7β-OHC) are implicated in the atheromatous plaque formation which contribute to several cardiovascular diseases and stroke ( Poli et al, 2013 , Wang et al, 2017 ). 7KC has also been found at increased level in patients with neurodegenerative diseases such as X-linked adrenoleukodystrophy (X-ALD) ( Nury et al, 2017 ), Alzheimer's disease ( Choroszyński et al, 2022 , Mahalakshmi et al, 2021 ), multiple sclerosis ( McComb et al, 2021 ), and Parkinson's disease ( Griffiths et al, 2021 ). In patients with age-related macular degeneration (AMD), high 7KC levels are also present in lipid deposits called drusens which are localized between the Bruch membrane and the basement membrane of retinal pigment epithelial cells ( Malvitte et al, 2006 , Rodríguez and Larrayoz, 2010 , Rodriguez et al, 2014 ).The cytotoxic properties of 7KC and 7β-OHC are exerted through stimulation of oxidative stress, activation of death pathways (apoptosis, autophagy) and cytokinic and non-cytokinic inflammation ( Vejux et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%